Autism and the myth of the person alone - Biklen, Douglas; Attfield, Richard (Qualitative studies in psychology., 2005)
Autism has been defined by experts as a developmental disorder affecting social and communication skills as well as verbal and nonverbal communication. It is said to occur in as many as 2 to 6 in 1,000 individuals. This book challenges the prevailing, tragic narrative of impairment that so often characterizes discussions about autism. Autism and the Myth of the Person Alone seriously engages the perspectives of people with autism, including those who have been considered as the most severely disabled within the autism spectrum. The heart of the book consists of chapters by people with autism.